Digitising farmer cooperatives to improve their financial and operational efficiency - Bappa Se, Marc Ghislain; Otim, Gerald; Gossaye, Elias; Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2019)
Agricultural and farmer cooperatives in ACP countries should replace current paper-based tools with digital solutions that will transform essential processes